Pengaruh Good Corporate Governance & Corporate Social Responsibility terhadap Kinerja Keuangan (The Influence of GCG and CSR on Financial Performance) - Sugeng Hariadi; Dina Rensita Putri; Djoko Sugiono (STIE Malangkucecwara, 2022)
This study aims to determine the effect of DKI (Independent Board of Commissioners), DD (Board of Directors), KI (Institutional Ownership), KM (Managerial Ownership), and CSR on the Financial Performance of the Mining Industry listed on the IDX in 2015-2019. Quantitative descriptive approach is the type of this research. With secondary data from the annual financial statements listed on the IDX through (www.idx.co.id) 2015-2019. With a sample of 17 companies from the mining industry taken by purposive sampling method. This study uses descriptive analysis techniques, simple & multiple linear hypothesis testing. This research results that the Independent Board of Commissioners, Institutional Ownership, and CSR have a significant positive effect on Financial Performance. Meanwhile, the Board of Directors and Managerial Ownership have no influence on the Company's Financial Performance.